1998
DOI: 10.1093/humrep/13.7.1936
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of potential users in Sicily towards preimplantation genetic diagnosis for beta-thalassaemia and aneuploidies

Abstract: This study aims to report the willingness of different populations of high-risk couples to undergo preimplantation genetic diagnosis (PGD) for beta-thalassaemia as an alternative to prenatal genetic diagnosis (PND), and the willingness of infertile couples to undergo PGD for aneuploidies. An information sheet and questionnaire presenting PGD and PND procedures were distributed to four population types: 54 high-risk couples for beta-thalassaemia coming for their first PND (population A); 51 similar couples comi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 20 publications
4
42
2
5
Order By: Relevance
“…Similar levels of support for PGD have been seen in populations outside the United States including Europe and Asia [16,17]. Although the majority of respondents supported PGD to identify genetic diseases, most did not support PGD for diseases that manifest late in life.…”
Section: Discussionmentioning
confidence: 59%
“…Similar levels of support for PGD have been seen in populations outside the United States including Europe and Asia [16,17]. Although the majority of respondents supported PGD to identify genetic diseases, most did not support PGD for diseases that manifest late in life.…”
Section: Discussionmentioning
confidence: 59%
“…[45][46][47][48] Roberts and Franklin 49 offer one of the few reports investigating factors in decision-making when using PGD and patients' choices made after genetic diagnoses are made. They found that patients make assessments before and throughout the entire PGD process including assessments of the costs of procedure and how their decisions are negotiated within familial and societal contexts, which parallels the outcomes of the meta-analysis.…”
Section: Acceptability Of Pgd Among High-risk Consumersmentioning
confidence: 99%
“…This preference has been observed before in couples with different genetic disorders, including cancer susceptibility syndromes as hereditary breast and ovarian cancer and familial adenomatous polyposis syndrome. [19][20][21][22][23] In a recent study among couples with a broad spectrum of genetic disorders, 74% of couples preferred PGD over PND for diagnostic testing in a future pregnancy. 24 The preference for PGD can partly be explained by the fact that PGD offers patients the possibility to have an unaffected genetically related child while termination of a pregnancy can be avoided.…”
Section: Discussionmentioning
confidence: 99%